Perkembangan Pesantren di Indonesia - Bella Almira Arjiarna; Yunani Hasan; Aulia Novemy Dhita (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
This writing aims to broaden the readers' insight where there are still many arguments or opinions about pesantren in Indonesia and find out how the development process of pesantren in Indonesia from the beginning of its emergence. Pesantren is one of the educational institutions that has long existed in Indonesia, some say that at first the pesantren did not originate from Islamic teachings, but there were also some experts who said that pesantren were already from Islamic teachings. Hopefully with this writing can be a teaching for the writer.